Adult functions for the Drosophila DHR78 nuclear receptor. Issue 2 (12th December 2017) - Marxreiter, Stefanie; Thummel, Carl S.
Abstract : Background: The Testicular Receptors 2 and 4 (TR2, TR4) comprise a small subfamily of orphan nuclear receptors. Genetic studies in mouse models have identified roles for TR4 in developmental progression, fertility, brain development, and metabolism, as well as genetic redundancy with TR2 . Here we study the adult functions of the single Drosophila member of this subfamily, DHR78, with the goal of defining its ancestral functions in the absence of genetic redundancy.Results: We show that DHR78 mutants have a shortened lifespan, reduced motility, and mated DHR78 mutant females display a reduced feeding rate. Transcriptional profiling reveals a major role for DHR78 in promoting the expression of genes that are expressed in the midgut, suggesting that it contributes to nutrient uptake. We also identify roles for DHR78 in maintaining the expression of genes in the ecdysone and Notch signaling pathways.Conclusions: This study provides a new context for linking the molecular activity of the TR orphan nuclear receptors with their complex roles in adult physiology and lifespan. Developmental Dynamics 247:315–322, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: DHR78 mutants have a shortened lifespan, reduced motility, and mated DHR78 mutant females display a reduced feeding rate. Transcriptional profiling reveals a major role for DHR78 in promoting the expression of genes that are expressed in the midgut. We also identify roles for DHR78 in maintaining the expression of genes in the ecdysone and Notch signaling pathways. This study provides a new context for linking the molecular activity of the TR orphan nuclear receptors with their complex roles in adult physiology and lifespan.